Bioprosthetic pulmonary valve endocarditis: Incidence, risk factors, and clinical outcomes. (17th September 2018) - Robichaud, Brian; Hill, Garick; Cohen, Scott; Woods, Ronald; Earing, Michael; Frommelt, Peter; Ginde, Salil
Abstract: Background: Pulmonary valve replacement (PVR) is a common operation in patients with congenital heart disease (CHD). As survival with CHD improves, infective endocarditis (IE) is a growing complication after PVR. The aim of this study was to assess the incidence, risk factors, and clinical outcomes of IE after surgical PVR in patients with CHD at our institution. Methods: Retrospective analysis of all cases of surgical PVR performed at Children's Hospital of Wisconsin between 1975 and 2016 was performed. All cases of IE after PVR were identified and clinical and imaging data were obtained by review of medical records. Results: Out of 924 surgical PVRs, there were 19 (2%) cases of IE. The incidence of IE after surgical PVR was 333 cases per 100, 000 person‐years. The median age at diagnosis of IE was 21 years (range = 1.2‐34 years) and the median time from PVR to diagnosis of IE was 9.4 years. The overall freedom from IE after PVR was 99.1%, 96.9%, and 93.4%, at 5, 10, and 15 years, respectively. There was no significant difference in freedom from IE based on valve type, including bovine jugular vein grafts. Patients with IE were more likely to have had a history of multiple PVRs, while length of follow‐up after PVR, age at time of PVR, and gender were not significant risk factors. Eleven (58%) cases of IE required surgical intervention, while 8 (42%) were successfully treated with intravenous antibiotics alone. There were no deaths and no recurrences of IE after treatment. Conclusion: The overall risk for IE after PVR is low. There was no association between age or type of pulmonary valve and risk of IE. The majority of cases require surgical intervention, but in general the outcomes of IE after PVR are good with low mortality and risk of recurrence.